Effects and mechanisms of Tieguanyin on the behavior of Alzheimer’s disease APP/PS1 mice - KANG Hyunuk; ZHOU Hui; YE Yushan; LIU Zhonghua; WEI Yuede; YANG Jiangfan; KIM Eunhye; HE Puming; LI Bo; WU Yuanyuan; TU Youying (浙江大学学报. 农业与生命科学版)
The effects of Tieguanyin extracts from different fragrance types (Qingxiang, Tgy-Q; Nongxiang, Tgy-N; and Chenxiang, Tgy-C) on the behavior of APP/PS1 double transgenic Alzheimer’s disease (AD) mice were studied, and the mechanisms of oxidative stress and inflammation were analyzed. Forty six-month-old female APP/PS1 mice were equally divided into five groups, which named as model group, donepezil group, Tgy-Q, Tgy-N and Tgy-C groups, and the control group consisted of 10 C57BL/6J mice. The drug was given by oral gavage for 70 consecutive days, and Y-maze test and open field test were performed during administration. At the end of the behavioral study, they were executed, and their plasma and brain tissue were collected, and then the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) content in plasma of mice were determined, and the morphological changes of glial cells were observed by immunohistochemical assay. The spontaneous alternation behavior rates of Tgy-Q, Tgy-N, Tgy-C extract treatments in the Y-maze experiment of mice groups were increased by 17.3%, 17.6% and 19.8% compared with the model group, respectively (P＜0.001), and the learning and memory abilities of mice in each group were significantly improved as compared with the model group. The results of open field test showed that the movement distances and residence time in the central area of mice fed with Tieguanyin extracts were significantly increased. The effective movement distances in the central area of mice was increased by 93.0% in the Tgy-C group (P＜0.001), followed by 82.0% in the Tgy-N group (P＜0.001) and 49.2% in the Tgy-Q group (P＜0.001). The optimal retention time in the central area of mice was 105.0% in the Tgy-C group (P＜0.01), followed by 84.1% in the Tgy-N group (P＜0.01), and 66.8% in the Tgy-Q group (P＜0.05). In the open field test, the spatial exploration ability and anxiety behavior of Tgy-C group were the best in all the treatments. In this experiment, oxidative stress levels of three Tieguanyin treatments were decreased, which are the main mechanisms of Tieguanyin against Alzheimer’s disease of APP/PS1 mice. Compared with the model group, the MDA contents of plasma in the Tgy-Q, Tgy-N, Tgy-C treatments were significantly reduced by 18.44%, 12.97% and 15.11%, respectively, and the SOD activities in the three groups were increased by 15.31%, 13.69% and 18.80%, respectively. Tieguanyin extracts also improved the morphological recovery of microglia and astrocytes in the brain of AD mice. The above research results indicate that three Tieguanyin extracts had a certain alleviating or protective effect on AD mice.